Rare-earth based nanomaterials and their composites as electrode materials for high performance supercapacitors: a review. Issue 8 (26th June 2020) - Liang, Shunfei; Wang, Huayu; Li, Yang; Qin, Huizhen; Luo, Ziyang; Huang, Biao; Zhao, Xun; Zhao, Chenglan; Chen, Lingyun
Abstract : In this review, we present recent reports on various rare-earth based nanomaterials and their composites for SCs and some challenges in the future. Abstract : The emergence of energy crisis and greenhouse effect has prompted people to develop energy storage equipment with excellent performance. Supercapacitors (SCs), also known as electrochemical capacitors, are widely studied for their high power density, fast charge and discharge and long cycle life. Rare earth is a group of elements with unique structure and properties. Rare earth-based nanomaterials, especially rare earth oxides, hydroxides and sulfides, have attracted much attention due to their good redox properties and environmentally friendly characteristics. Rare earth-based SCs nanomaterials can be obtained by environmentally friendly, simple and low-cost methods, such as hydrothermal/solvothermal method, electrodeposition method, atomic layer deposition method, etc. This paper reviews the synthesis methods, morphology and electrochemical properties of various rare earth-based nanomaterials and their composites for SCs. Finally, based on the reported literature, we discussed some challenges faced by rare earth-based nanomaterials and the issues that need attention in SCs and other electrochemical energy storage fields in the future.